2021
DOI: 10.48550/arxiv.2106.06520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tidal excitation as mixing in thermal CFT

Julius Engelsöy,
Bo Sundborg

Abstract: We use mixed correlators in thermal CFT as clean probes of the strong gravity effects in their holographic duals. The dual interpretation of mixing is an inelastic conversion of one field to another field, induced by gravity: tidal excitation. We find an enhanced mixing at high temperatures, corresponding to large AdS black holes, concentrated to small boundary momenta, dual to the deep bulk, where strong gravitational fields are expected. We also find large O(1/G N ) tidal conversion in the low temperature ph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In [21] the authors showed that the string is also tidally excited along directions of T 4 . For other works on tidal forces in the context of AdS/CFT see [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In [21] the authors showed that the string is also tidally excited along directions of T 4 . For other works on tidal forces in the context of AdS/CFT see [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as we will discuss, the correction in fig. (1) is actually the leading term for offdiagonal correlators (an issue recently discussed in [15]). Recall that at T = 0 conformal symmetry sets to zero 2-point functions for operators of different conformal dimensions.…”
Section: Introduction and Conclusionmentioning
confidence: 99%
“…(1), they "explore inside the horizon". Thus, it would be very interesting to further study off-diagonal correlators, specially in connection to [15]. This paper is organized as follows: in section 2 we set up the holographic computation of 2-point functions in our toy model, whose leading terms are captured by the Witten diagram expansion in fig.…”
Section: Introduction and Conclusionmentioning
confidence: 99%